Edukasi Risiko Mengkonsumsi Minuman Kemasan Terhadap Penyakit Diabetes Mellitus di SMP N 1 Darul Imarah Aceh Besar - Aroni, Defri; Sari, Amelia; Malina, Tanzilal; Maulana, Iska; Helda, Hidayani; Ronaldo, Leo; Zakaria, Nurmalia; Fauziah (Universitas Baiturrahim, 2025)
High-sugar packaged beverage consumption is a common habit among adolescents and contributes to the growing risk of early-onset Diabetes Mellitus. This community service activity aimed to increase students’ knowledge regarding the risks of packaged drinks through interactive health education. The activity was conducted at SMP Negeri 1 Darul Imarah, Aceh Besar, involving 23 eighth-grade students. The educational intervention included lectures, group discussions, and nutrition label reading simulations. Evaluation was carried out using pretest and posttest instruments. The results showed a significant increase in the students’ average knowledge scores from 55.2 to 82.6. The program also raised awareness about limiting added sugar intake and choosing healthier beverages. This activity demonstrated that contextual health education is effective in improving nutrition literacy and preventing non-communicable diseases from an early age